The effect of silicon content on liquid-metal-embrittlement susceptibility in resistance spot welding of galvanized dual-phase steel. (September 2020) - Ghatei Kalashami, A.; DiGiovanni, C.; Razmpoosh, M.H.; Goodwin, F.; Zhou, N.Y.
Graphical abstract: Highlights: Increasing Si content increased liquid-metal-embrittlement susceptibility. Increasing Si content caused earlier expulsion during resistance spot welding. Increasing Si content increased depth of decarburization layer and ferrite grain size during continuous galvanizing process. Abstract: Liquid metal embrittlement (LME) can have a significant effect on the mechanical properties of resistance spot welding (RSW) advanced high strength steels (AHSS). An understanding of the role of alloying elements such as silicon (Si) on microstructure details and RSW parameters, both of which influence LME cracking is essential for design of LME-resistant AHSS. The present study has shown that increasing Si-content from 0.7 wt.% to 1.8 wt.% increased LME susceptibility in dual phase (DP) steels. It has been demonstrated that increasing Si led to higher heat inputs and early expulsion due to the higher resistivity of the higher Si-content grade during RSW that was related to more severe LME-cracking. Furthermore, increasing Si-content had a significant effect on microstructural evolution during processing prior to RSW, including increased ferrite grain size, decarburization layer depth, and internal oxides density, all of which were related to an increased LME crack susceptibility.